EFEKTIVITAS PENGGUNAAN APLIKASI C++ PADA HP DAN KOMPUTER DALAM MENINGKATKAN KEMAMPUAN PEMROGRAMAN DASAR SISWA KELAS X SMAK CITRA BANGSA MANDIRI KUPANG - Mumur, Veronika Idelsi; Jhon Enstein; Diana Yanni Ariswati Fallo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Veronika Idelsi Mumur, 2025: Effectiveness of Using C++ Applications on Mobile Phones and Computers in Improving Basic Programming Skills of 10th-grade Students at SMAK Citra Bangsa Mandiri Kupang. Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang. Supervisors: Mr. John Einstein, S.Kom., M.CS., and Ms. Diana Y.A. Fallo, S.Kom., M.T. This study used a quantitative method with an experimental design (Experimental Class and Control Class). The experimental class (XC) received treatment using the Programiz C++ application on a mobile phone, while the control class (XD) used the Dev C++ application on a computer. Data were collected through pre-test and post-test instruments. Data analysis used an Independent Sample T-Test to determine the difference in learning outcomes between the two groups. The results showed a significant difference in average learning outcomes between the group using mobile phones and the group using computers, with a significance value (Sig. 2-tailed) of 0.004 (p < 0.05). The average posttest score for the experimental class (mobile phones) was 85.75, significantly higher than the control class (computers), which had an average of 75.25. This improvement indicates that using the Programiz C++ application on mobile phones is more effective than using Dev C++ on computers.